Peculiarities of the University’s Educational Environment Implementation in the Organization of Future Teachers’ Pedagogical Practice - M. A. Chervonnyy; A. A. Vlasova; T. V. Shvaleva; T. T. Gazizov (Высшее образование в России)
The article addresses contradictions between the existing and predicted tendencies in the organization and content of pedagogical practices. Through the analysis of teacher training programs, the need for student educational practice has also been established, which provides a solution to a wider range of professional tasks. The revealed contradictory nature made it possible to formulate the problem: what can be a trigger for the initiative acquisition by a future teacher of the experience in solving professional problems? Primary attention in solving this problem is paid to the conditions for the manifestation of personal student initiatives: the creation of platforms for dialogue, the provision of a periodic process of transition from practice to theory and vice versa, the use of operators of semiotic diagnostics of changes in students’ personal interests. The article presents the experience of organizing the educational environment, which provides future teachers with a modern range of professional probation. The options for the organization of official student practice are presented, including the development of online classes of educational and leisure activities of schoolchildren. This model contributes to the manifestation of students’ personal initiatives, both within the training profile and in the sphere of interdisciplinary intersections. The authors adduce the results of the questionnaire survey of students after the practice, showing their satisfaction with the chosen profession, a high level of motivation for mastering professional actions. The main methods and directions of organizing practices have been determined. They make it possible to ensure the predicted level of solving professional tasks by graduates.